Peran Petugas Kesehatan Dalam Menangani Scabies Pada Anak Di Lembaga Pembinaan Khusus Anak (LPKA) Kelas 1 Kutoarjo - Tegar Karunia Esa; Umar Anwar (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2022)
Scabies is a parasitic skin disease caused by the parasite Sarcoptes scabies. Many underdeveloped countries, including Indonesia, suffer from scabies. Scabies is very common among children and adolescents. Scabies is an infectious disease that is influenced by the presence or absence of scabies risk factors in a person. Scabies is very common among those who live in close quarters. The purpose of this study was to see whether there was a relationship between children's personal hygiene and the incidence of scabies. An analytical observational study with a cross sectional research strategy was used in this study. The data used is primary data. Data collection was obtained from health workers who were at the Lembaga Pembinaan Khusus Anak Kelas I Kutoarjo. Keywords : role, treatment, scabies